Analysis of Production and Inventory Control of Batik Raw Materials According to Islamic Economic Perspective (Case Study at SME Santi Batik) - Ratina Fitri; Eka Sri Wahyuni; Yenti Sumarni (UNIVED Press, 2024)
This study aims to find out how the batik production process and batik raw material inventory control in UKM Santi Batik using the EOQ (economic order quantity) method, safety stock, reorder point and total cost. . In this study, researchers used a descriptive-comparative method with a quantitative approach and used primary data collection techniques in the form of a questionnaire specifically for UKM Santi Batik. The data analysis technique used is the approah formula, namely the method of determining the number of economic orders by reducing them in the formulas. The results of the research and discussion can be concluded that the EOQ (economic order quantity) method is more effectively used in raw material inventory control than the existing policies in UKM Santi Batik. Because UKM Santi Batik has not used optimal raw material inventory control, namely only using estimates in purchasing batik raw materials. In addition, by using safety stocks, UKM Santi Batik can avoid shortages of raw materials in production, reorder points so that UKM Santi Batik knows when to buy raw materials again and obtain them with minimum total inventory costs.